OCULAR DISEASE IN CHILDREN WITH TYPE 1 DIABETES - Basílio, Ana Luísa (2017)
Specialized care provided to diabetic patients, in developed countries, has contributed to the reduced number of ocular complications in pediatric age. The effectiveness of annual eye examinations in this group is unclear. The authors intend to determine the prevalence and onset of ocular disease in this population and adapt the results to the dynamics of a tertiary center, based on a retrospective study of type 1 diabetes patients’ medical records registered and monitored in Pediatric Endocrinology Department of Centro Hospitalar de Lisboa Central, between January of 2008 and July of 2015. Demographic characteristics, underlying and ocular disease, referral and follow-up of these patients in the Pediatric Ophthalmology Department were evaluated. Medical records of 304 patients with type 1 diabetes were analyzed. 110 patients referred to Ophthalmology Department had been included in the study. The mean age was 13.2 years (4-20 years), 57 were male and 53 female. Type 1 diabetes was diagnosed at 7.5 years on average (0.75-13 years) and mean disease duration was 6.0 years (1-14 years). The average of the last hemoglobin A1c value was 8.6% (4.9-14.4%). The first eye exam was performed at 9.4 years on average (2-19 years), in 55 cases the patients had less than 10 years and, of those, 29 were referred in the first year after diagnosis (mean duration diabetes of 2.0 years; 0-7 years). Regarding the 55 patients older than 9 years, 27 were referred in the first year after diagnosis (mean duration of diabetes 2.3 years, 0-9 years). In 54 patients ophthalmological exam was repeated after 1 year, 15 after 2 years, 1 after 3 years and 1 after 5 years. No diabetic retinopathy cases were found. 28 astigmatism, 12 hyperopia, 16 myopia, 5 strabismus, 2 blepharoptosis and 1 polar cataract were diagnosed. International Society for Pediatric and Adolescent Diabetes recommend ophthalmological initial screening 2 years after the diagnosis of type 1 diabetes, in patients above 10 years, and 5 years after, if lower ages. American Academy of Ophthalmology 2014 guidelines recommend that the first eye examination should begin 5 years after the diagnosis and repeated annually. A previous study conducted at Hospital Dona Estefânia, between 1999 and 2000, by Rodrigues P et al has described a low incidence of ocular lesions (6.4%) in the studied population, being in agreement with our results. Recent published studies are also consistent and demonstrate that the rare incidence of ocular complications of diabetes until puberty can justify new guidelines in the coming years.